1973
DOI: 10.1111/j.1399-6576.1973.tb00839.x
|View full text |Cite
|
Sign up to set email alerts
|

The Fate of Pancuronium Bromide in Man

Abstract: The fate of pancuronium bromide has been investigated in 20 anaesthetized patients, seven undergoing cholecystectomy with choledochostomy (Group I), seven undergoing cholecystectomy only (Group 11) and six undergoing pelvic operations (Group 111). A fluorimetric method was used to determine pancuronium bromide and its bis-quaternary derivatives in blood, urine and bile. After a single intravenous injection of 6 mg pancuronium bromide, disappearance of the drug from the plasma proceeded in three phases with hal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

1977
1977
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(21 citation statements)
references
References 16 publications
(11 reference statements)
1
20
0
Order By: Relevance
“…Pharmacokinetic studies with pancuronium in surgical patients have also indicated that this agent shows pronounced muIticompartment behaviour (Agoston et al, 1973;Buzello, 1975;Gibaldi et al, 1971;Mcleod et ai., 1976;Somogyi et al, 1976). Agoston and associates (1973) noted the presence of a terminal elimination phase (t1/2 = 108 to 147 minutes), together with 2 residual phases, when plasma concentration data for pancuronium was plotted against time.…”
Section: Pancuroniummentioning
confidence: 97%
See 2 more Smart Citations
“…Pharmacokinetic studies with pancuronium in surgical patients have also indicated that this agent shows pronounced muIticompartment behaviour (Agoston et al, 1973;Buzello, 1975;Gibaldi et al, 1971;Mcleod et ai., 1976;Somogyi et al, 1976). Agoston and associates (1973) noted the presence of a terminal elimination phase (t1/2 = 108 to 147 minutes), together with 2 residual phases, when plasma concentration data for pancuronium was plotted against time.…”
Section: Pancuroniummentioning
confidence: 97%
“…The biliary elimination of pancuronium accounts for about 6 % of the dose as intact drug (Agoston et al, 1973;Buzello, 1975). Metabolism, presumably hepatic, has also been shown to occur.…”
Section: Elimination (Excretion and Metabolism)mentioning
confidence: 99%
See 1 more Smart Citation
“…Vecuronium and pancuronium are both steroidal substances, with vecuronium being the monoquaternary homologue of pancuronium (Savage et al 1980). Both muscle relaxants are taken up by the liver and metabolized to hydroxy-derivatives (Agoston et al 1973;Booij et al 1981). Atracurium, on the other hand, has a different chemical structure which is derived from the benzylisoquinolinium molecule.…”
Section: Discussionmentioning
confidence: 99%
“…I n addition, other factors, such as species differences, are also likely to be involved. Biliary excretion of pancuronium was reported to be unimportant in the rat both in uivo ) and in uitro (MEIJER & WEITERINC 1970), but appreciable in man (AGOSTON et al 1973b).…”
Section: Discussionmentioning
confidence: 99%